Top decision-making bodies in large companies: Gender quota shows initial impact on supervisory boards executive board remains a male bastion - Elke Holst; Katharina Wrohlich (DIW Economic Bulletin, 2017)
The gender quota for supervisory boards that has been mandatory since January 2016 has shown an initial impact. According to DIW Berlin's Women Executives Barometer, at the end of 2016, there were more women on the supervisory boards of the 106 companies subject to the statutory quota than one year before. Their proportion increased by a solid four percentage points to more than 27 percent. And in the other groups of companies studied, the number of female supervisory board members also rose. However, the calculations based on the top 200 companies also showed that in companies in which the supervisory board already consisted of one-third women, the proportion hardly increased or did not increase at all. The gap between supervisory and executive boards has also widened because growth in the latter has flattened. Women represent only 6,5 percent of the executives at companies subject to the quota - even fewer than in the DAX 30 (11 percent) and the average of the 200 highest performing companies in Germany (eight percent). In companies with government-owned shares, the momentum has decreased significantly - they run the risk of losing their function as role models. To forestall a tightening of the law, companies should ensure more balanced gender representation on all executive levels.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executive boards; CEOs; women